PENGARUH MARKETING MIX DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK ES KRIM MIXUE CABANG PABUARAN KABUPATEN BOGOR - Rahmawati, Andita; Kamil, Musthafa (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2025)
It's no surprise to hear the word Mixue again, many people flock to feel the pleasure of Mixue ice cream, people are willing to queue long to get the ice cream. This research aims to influence how much influence the Marketing Mix and service quality have on the decision to purchase ice cream products. mixue. The researcher used two variables, namely the independent variable which includes Marketing Mix (X1), and Service Quality (X2), as well as Purchase Decision (Y) as the dependent variable. The research was conducted on mixue customers at the Pabuaran branch in Bogor Regency with 100 respondents using the Nonprobability Sampling method, by selecting Purposive Sampling with quantitative methods. The data collection method uses observation and questionnaires with data processing using SPSS version 25. Based on the results of the Partial Marketing Mix Test on Purchasing Decisions, the value is 0.781 > 0.05 and the calculated t value is 0.279 < t table 1.98472 so that H1 is rejected, meaning it does not exist. The influence of Marketing Mix on Purchasing Decisions, testing H2 shows that the significance value for the influence of Service Quality on Purchasing Decisions is 0.000 < 0.05 and the t value is 7.715 > t table 1.98472 so it can be said that H2 is accepted. However, simultaneously the influence of Marketing Mix and Service Quality on Purchasing Decisions gets a significance value of 0.000 < 0.05 and a calculated f value of 30.141 > f table 2.043 so that H3 can be accepted